Twenty-five years of Cardiac Surgery in Nepal: Trials, Tribulations and Triumph - Rajbanshi, Bijoy G; Pradhan, Sidhartha; Koirala, Bhagawan (Nepalese Heart Journal, 2022)
Twenty-five years ago, embarked the start of the era of cardiovascular surgery using the heart lung machine in the country and as we celebrate this humble beginning, we sought to review the advent and the progress made in this field of science over the course of the years in the country; delve in to the challenges and opportunities that it may present in the future to uphold this great profession.